Determining the robustness of an interdependent network with a hypergraph model - Gholam Hasan Shirdel; Ameneh Mortezaee (Electronic Journal of Graph Theory and Applications (EJGTA), 2020)
The world is included of various entities and complex interdependencies between them that can be appeared in multi-layered networks. It may be the acting of some of these entities depends on the acting of the others such that the failure in one entity may cause failures in a number of others. In this paper we try to model these complex interdependencies in a interdependent network with a directed hypergraph model and then we propose an algorithm to determine minimum number of failure for total failure in the power grid and communication network as a special interdependent network.